Young Adult’s Online Shopping Behavior: A Case on Malaysian Perspective - Yoo, Mei Teen (2013)
Prior research focused on online shopping behavior of various different age groups including young adults. Yet, the impact of peer influence when young adults’ make the decision to shop online has not been explored in the context of Malaysia. In order to fill this gap, this study extends the previous research by exploring the impact of peer influence on internet and online shopping behavior among young adults in Malaysia. The theoretical lens used in viewing the research is unified theory of acceptance and use of technology (UTAUT) model and normative social influence theory. The respondents are sought from universities based in the Klang Valley area of Malaysia. The questionnaires were distributed to young adults’ aged 18-24 using convenient sampling. The hypotheses of the research were tested using PLS estimation technique version 2.0 whereas the descriptive analysis profile was done using SPSS statistical software version 20. This research revealed that peer influence has a significant impact on young adults’ decision on shopping online. The study also established that the four factors of UTAUT (performance expectancy, effort expectancy, social influence, and facilitating conditions) have a significant influence on online shopping behavior of young adults in Malaysia. The discussion explains the empirical evidence. Practical and theoretical implications are further highlighted. Recommendations for future research are also provided.